THE USE OF ICT IN “DISCRETE MATHEMATICS” METHODICAL SYSTEM OF EDUCATION FOR THE FORMATION OF INFORMATION COMPETENCE - Azadova, E.V. (Journal of Information Technologies in Education (ITE), 2012)
The article deals with the implementation of information and communication technologies in educational system of "Discrete Mathematics" as a way to formation of students’ information competence.